COOLING SYSTEM OF ROCKET NOZZLES - Alimjonov Islom; Abdusamadov Abdushoir (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: The purpose of studying this topic is to study in detail the cooling system of launcher nozzles. A comparison of the cooling systems of today's launch vehicles and the launch vehicles of the last century and an evaluation of the revolutionary process.